Evaluation of green waste, green waste compost and cow dung as amendments for white wine distillers' grains vermicomposting - Gong, Xiaoqiang (Environmental technology, 2024)
The application of organic additives is an efficient strategy to promote the vermicomposting of organic wastes. This study investigated the changes in earthworm growth, nutrients, enzyme activities, microbial composition, and seedling growth during 60 days of vermicomposting of white wine distillers' grains (WWDG) mixed (50:50, w/w) with green waste (GW), green waste compost (GWC), or cow dung (CD). Our data showed that GW, GWC, and CD addition significantly enhanced the survival rate (73.33%-89.17%), growth, and reproduction of earthworms compared to the control treatment. The degradation rate of TOC, the increasing rate of nutriments (total N, total P, total K, available P, available K, humic acid, NH4+, NO3-), and the germination index were significantly higher in the additive treatments than in the control treatment. Dehydrogenase, phosphatases, and urease activities were significantly elevated in the vermicompost amended with additives. The additives remarkably stimulated bacteria, such as Streptomyces, Steroidobacter, Bacillus, Luteibacter, and Rhodanobacter, etc., which were closely related to the biocontrol of phytopathogens and the decomposing recalcitrant substances. Moreover, additives significantly promoted the generation and growth parameters of tomato and lettuce seedlings when compared with the control. In summary, these results indicated that all three additives facilitated the vermicomposting of WWDG and improved the compost quality by enhancing earthworm and enzyme activities as well as altering compost bacterial community, especially when the GWC addition yields the best compost quality and shows strong potential for future application. This study developed a new method for improving WWDG utilization rate and it will promote organic waste recycling in China